Spectroscopic Diagnosis of Arc Carbon and Magnesium Plasma - Hussein, Nada K.; Kadhem, S. J. (Iraqi Journal of Science, 2022)
This research aims to investigate parameters for magnesium (Mg)  carbon (C), and carbon/magnesium plasma produced by the exploding electrical wire (EEW) technique. In this work, C and Mg nanoparticles were synthesized. The plasma spectra with three different current values (50, 75 and 100A) were recorded using optical emission spectroscopy (OES). The plasma electron temperature (Te), electron density (ne), plasma frequency (fp), Debye length (ℷD), and Debye number (ND) provided by arc discharge plasma were  calculated. Boltzmann plots were  used to calculate the electron temperature (Te); electron density (ne) was calculated by Stark broadening . The results showed that the electron temperature and electron density increased with the increase of current.  For carbon plasma, Te increased from (1.243 to 1.533) eV, and ne increased from (8.762 to 9.857) cm-3. Te for magnesium plasma increased from (0.508 to 0.724)eV  and ne increased from(6.700 to 10.420) cm-3. When the magnesium strip was exploded in carbon suspension, Te  increased from (0.744 to 0.851) eV, and electron density was raised from (5.738 to 9.304)cm-3.